Resilience of Indonesian Plantation Commodity Exports to Global Geopolitical Shocks - M. Farandika Akbar; Yudika Ester Kejutini Sigiro; Erwin Efendi Nasution; Muhammad Febriansyah Ibrahim (JASc (Journal of Agribusiness Sciences), 2026)
This study evaluates the export resilience of Indonesia's key plantation commodities which is Technically Specified Natural Rubber (TSNR), Crude Palm Oil (CPO), and coffee by integrating Revealed Comparative Advantage (RCA), Trade Specialization Index (TSI), and Export Product Dynamics (EPD) indicators from 2010 to 2024. The empirical findings reveal a systematic degradation in export competitiveness, particularly for TSNR, while CPO and coffee exhibit dynamic but fragile resilience in the face of global macroeconomic shocks. The study highlights that Indonesia's export position is increasingly vulnerable to geopolitical transmission risks, notably the potential escalation of the Iran–Israel–US conflict. Such instability threatens to trigger systemic convergence toward the "Retreat" quadrant due to disruptions in maritime logistics and global demand contraction. These findings underscore the urgent need for strategic market diversification and value chain strengthening to mitigate the looming threats of global trade fragmentation.